Social context modulates the behavioural effects of physical enrichment in yellowfin seabream Acanthopagrus latus - Yijie He; Zonghang Zhang; Yating Zheng; Wuhan Lin; Wentao Lu; Qiaoling Fu; Wenhua Liu (Applied Animal Behaviour Science, 2026)

Effectiveness of Conditioning Strategies in Improving Fish Fitness‐Related Traits - Zonghang Zhang; Guihui Ning; Fei Tong; Wuhan Lin; Yangke Shang; Daomin Peng; Wenhua Liu (Fish and Fisheries, 2025)
Although conditioning strategies are widely used to increase fish post‐release adaptability in stock enhancement projects, their effectiveness has not been systematically evaluated. Using a global‐scale meta‐analysis, we demonstrate that three major conditioning strategies, including environmental enrichment, life skills training and release tactic, can significantly improve fish fitness‐related traits, with the fitness indicator and developmental stage being the most important moderators for interpreting the high heterogeneity among cases. The effect size of approximate fitness indicators was marginally lower than that of post‐release behavioural traits. Our findings indicate the necessity of conditioning procedures and highlight the need to enact context‐dependent strategies in practical conservation projects.

Aquaculture environment changes fish behavioral adaptability directly or indirectly through personality traits: a case study - Zonghang Zhang; Wuhan Lin; Dongjian He; Quanming Wu; Canrui Cai; Huaxuan Chen; Yangke Shang; Xiumei Zhang (Reviews in Fish Biology and Fisheries, 2023)

Physical enrichment for improving welfare in fish aquaculture and fitness of stocking fish: A review of fundamentals, mechanisms and applications - Zonghang Zhang; Wuhan Lin; Yunqi Li; Xianyu Yuan; Xianqing He; Hancheng Zhao; Jiezhang Mo; Jianqing Lin; Liangliang Yang; Bo Liang; Xiumei Zhang; Wenhua Liu (Aquaculture, 2023)